Multilayer electrode-electrolyte assembly and method for producing the same

By using high-pressure hot pressing method to prepare multi-layer components in electrochemical cells, the problems of combustion and dendritic formation during sintering of solid cathode materials are solved, and the battery components with high density and high contact interface are realized, which improves the safety of the battery and performance.

CN113785426BActive Publication Date: 2025-02-25HYDRO QUEBEC CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202080032804.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-31
Filing Date
2020-05-01
Publication Date
2025-02-25
Estimated Expiration
2040-05-01

AI Technical Summary

Technical Problem

The prior art is prone to material combustion and dendrites when preparing solid-state battery pack components, especially during the sintering process of cathode materials, and there are still difficulties in preparing solid-state cathodes.

Method used

A method of preparing multilayer components, including preparing a solid electrolyte layer by compressing ceramic particles and applying a mixture containing electrochemically active materials, ceramic particles and electronically conductive materials on the electrolyte layer, followed by high voltage and specific temperatures Prepare by hot pressing, avoiding the use of polymers and solvents.

Benefits of technology

The high density and tight fusion interface of the solid-state battery pack assembly are realized, which improves the safety and performance of the battery and avoids the problems of polymer residue and solvent residue.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003331576810000011
    Figure HDA0003331576810000011
  • Figure HDA0003331576810000021
    Figure HDA0003331576810000021
  • Figure HDA0003331576810000031
    Figure HDA0003331576810000031
Patent Text Reader

Abstract

The present invention relates to multilayer assemblies comprising a solid electrolyte layer and a solid electrode layer, both of which contain ceramic particles and are free of polymers, and to electrochemical cells containing them. Also disclosed is a method for preparing these multilayer assemblies, which method uses a hot pressing step.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Related Applications

[0002] This application claims priority under applicable law to U.S. Provisional Patent Application Nos. 62 / 842,963 and 62 / 955,679, filed on May 3, 2019 and December 31, 2019, respectively, the contents of which are incorporated herein by reference in their entirety for all purposes.

[0003] The present invention relates generally to methods for preparing solid-state multilayer components comprising electrode layers and electrolyte layers, to components obtained by these methods and to electrochemical cells comprising them. Technical Background

[0004] Liquid electrolytes based on flammable liquids such as ethylene carbonate or diethyl carbonate, which are widely used in lithium-ion batteries, can ignite, for example, when the temperature in the battery increases (Guerfi ​​et al., J. Power Soruce 195, 845–852 (2010)), and therefore often result in unsafe batteries. These liquid electrolytes also lead to dendrite growth and require the use of separators, with varying degrees of success.

[0005] Solid electrolytes have been developed, for example based on polymers (mainly based on polyethylene oxide, see Commarieu et al., Curr. Opin. Electrochem. 9, 56–63 (2018)), or based on ceramics, such as gallium-doped cubic Li7La3Zr2O 12 (LLZO) (see Rawlence et al., ACS Appl. Mater. Interfaces 10, 13720–13728 (2018)), NASICON type Li 1.5 Al 0.5 Ti 1.5 (PO4)3(LATP) (see Soman et al., J. Solid State Electrochem. 16, 1761–1766 (2012)), NASICON type Li 1.5 Al 0.5 Ge 1.5 (PO4)3(LAGP) (see Zhang et al., J. Alloys Compd. 590, 147–152 (2014)) and Li 4-x Ge 1-x P xS4thio-LISICON (see Kanno & Murayama, J. Electrochem. Soc. 148, 742–746 (2001)). Hybrid solid electrolytes based on ceramics and polymers can also be used to obtain improved mechanical strength and ionic conductivity (Wang et al., ACS Appl. Mater. Interfaces 9, 13694-13702 (2017)).

[0006] The densification of solid electrolytes is a key element to prevent the formation of lithium metal dendrites. It is shown that the use of hot pressing as a tool can reduce the grain boundary resistance in LLZO electrolytes (see David et al., J.Am.Ceram.Soc.1214,1209-1214 (2015)). However, the best results presented are obtained at a temperature of up to 1100 ° C. Some teams have reported hot pressing methods to densify NASICON-type LAGP solid electrolytes. A multi-step method has been described for the densification of LAGP, including hot pressing at 600 ° C under argon at a pressure of 20 MPa, followed by a step of sintering at 800 ° C in air for 8 hours to form LAGP rods (see Kotobuki et al., RSC Adv., 11670-11675 (2019)). The rod is then sliced ​​with diamond wire to provide a thin electrolyte membrane.

[0007] Still, the ultimate preparation of solid-state cathodes remains difficult, as sintering of cathode materials in the presence of oxygen is likely to burn off any carbon present. In 2018, another team described a Li-based 1.3 Al 0.3 Ti 1.7 (PO4)3 all-phosphate-based battery (Yu et al., ACS Appl. Mater. Interfaces 10, 22264-22277 (2018)). In this case, the authors prepared LATP electrolyte pellets by cold pressing, followed by sintering at 1100 ° C in an air atmosphere. Then, LiTi2(PO4)3, LiO2 in NMP as a solvent were repeatedly spread by screen printing. 1.3 Al 0.3 Ti 1.7 The electrolyte layer was prepared by drying a suspension consisting of (PO4)3, carbon black and ethyl cellulose as a binder (45:25:15:15). The cathode was prepared according to the same method, but LiTi2(PO4)3 was replaced by Li3V2(PO4)3. The battery was then subjected to cold isostatic pressing at 504MPa for 30 seconds and then dried at 120°C.

[0008] The cold sintering method of independently preparing solid electrolytes and solid electrodes using various materials was also reviewed in Liu et al., J. Power Sources 393, 193–203 (2018), and the results were quite different.

[0009] Therefore, new methods for preparing solid-state battery pack components are needed that improve at least one aspect of the foregoing methods. SUMMARY OF THE INVENTION

[0010] This disclosure relates to a method of preparing a multilayer component and an electrochemical cell comprising such a component, to a multilayer component prepared by the method, and to an electrochemical cell and battery pack containing them.

[0011] According to one aspect, a method of preparing a multilayer component comprising a solid electrode layer and a solid electrolyte layer comprises at least the steps of:

[0012] a) preparing a solid electrolyte layer by compressing ceramic particles;

[0013] b) preparing a mixture comprising at least an electrochemically active material, ceramic particles, and an electronically conductive material, the mixture being solvent-free;

[0014] c) applying the mixture obtained in (b) onto the solid electrolyte layer prepared in (a) to obtain a bilayer material;

[0015] d) pressing the bilayer material obtained in (c) at a pressure of at least 50 kg / cm 2 and at a temperature in the range of about 400 °C to about 900 °C.

[0016] In one embodiment, step (a) does not include adding a solvent. In another embodiment, step (a) does not include adding a lithium salt. In a further embodiment, neither the solid electrolyte layer nor the electrode layer contains a polymer after step (d). According to another embodiment, step (b) also does not include adding a solvent. According to some embodiments, the mixing step (b) is carried out by ball milling.

[0017] In another embodiment, the ceramic of step (a) has the formula Li 1+z Al z M 2-z (PO4)3, where M is Ti, Ge, or a combination thereof, and z is such that 0 < z < 1. In one embodiment, M is Ge. In another embodiment, M is Ti. According to a further embodiment, step (a) is carried out in the presence of oxygen (e.g., in air). In yet another embodiment, step (a) is carried out at a pressure of 100 kg / cm 2 to 5000 kg / cm 2 .

[0018] In a further embodiment, step (d) is carried out in an inert atmosphere (e.g., argon, nitrogen). In another embodiment, step (d) is carried out at 50 kg / cm 2 Up to 5000kg / cm 2 , or 100kg / cm 2 Up to 5000kg / cm 2 , or 300kg / cm 2 Up to 2000kg / cm 2 In yet another embodiment, step (d) is performed at a temperature of about 450°C to about 850°C or about 600°C to about 700°C. In another embodiment, step (d) is performed for a time greater than 0 hours and less than 10 hours, or 30 minutes to 5 hours, or 30 minutes to 2 hours.

[0019] In one embodiment, the electrode layer is a positive electrode layer. In one embodiment, the electrochemically active material in the electrode layer is selected from phosphates (e.g., LiM a PO4, of which M a Fe, Ni, Mn, Co or a combination thereof), oxides and composite oxides, such as LiMn2O4, LiM b O2(M b is Mn, Co, Ni or a combination thereof) and Li (NiM c )O2(M c is Mn, Co, Al, Fe, Cr, Ti, Zr or a combination thereof), elemental sulfur, elemental selenium, iron (III) fluoride, copper (II) fluoride, lithium iodide and iodine. For example, the electrochemically active material of the positive electrode can be a phosphate LiM a PO4, of which M a is Fe, Mn, Co or a combination thereof (eg LiFePO4), wherein the electrochemically active material is made of particles which are optionally further coated with carbon.

[0020] According to other embodiments, the electronically conductive material in the electrode layer is selected from carbon black, Ketjen TM Black (Ketjen TM black), acetylene black, graphite, graphene, carbon fibers or nanofibers (such as VGCF), carbon nanotubes, and combinations thereof. For example, the electronically conductive material comprises carbon fibers (such as VGCF).

[0021] In another embodiment, the ceramic particles of step (b) comprise the formula Li 1+z Al z M 2-zA ceramic of (PO4)3, where M is Ti, Ge, or a combination thereof, and 0 < z < 1. In one instance, M is Ge. In another instance, M is Ti.

[0022] In a related embodiment, the ceramic of step (a) and the ceramic particles of step (b) are the same.

[0023] According to another aspect, the present disclosure relates to a method for preparing a multilayer assembly comprising a solid electrode layer and a solid electrolyte layer, the method comprising at least the steps of:

[0024] a) preparing an electrolyte composition layer by applying a mixture of ceramic particles and a polymer on a first carrier;

[0025] b) preparing a mixture comprising at least an electrochemically active material, ceramic particles, an electronically conductive material, and optionally a polymer;

[0026] c) applying the electrode material mixture prepared in step (b)

[0027] i. on the electrolyte composition layer prepared in step (a); or

[0028] ii. on a second carrier and then bringing the surface of the applied electrode material mixture into contact with the surface of the electrolyte composition layer;

[0029] to provide a bilayer material;

[0030] d) pressing the bilayer material obtained in step (c) at a pressure of at least 50 kg / cm 2 and a temperature of about 400 °C to about 900 °C.

[0031] In one embodiment, step (a) of the method does not include adding a solvent. Alternatively, step (a) of the method further includes a solvent and further includes drying the mixture after application. In another embodiment, step (a) further includes removing the first carrier. In yet another embodiment, step (a) does not include adding a lithium salt. According to one embodiment, the polymers in steps (a) and (b), if present, are independently selected, each time they occur, from fluorinated polymers (such as polyvinylidene fluoride (PVDF) or poly(vinylidene fluoride - co - hexafluoropropylene) (PVDF - HFP)), poly(alkylene carbonate) (such as poly(ethylene carbonate) or poly(propylene carbonate)), polyvinyl butyral (PVB), or polyvinyl alcohol (PVA). For example, the polymer is poly(alkylene carbonate) (such as poly(ethylene carbonate) or poly(propylene carbonate)).

[0032] According to a further embodiment, the solid electrolyte layer and the electrode layer are free of polymer after step (d).

[0033] In another embodiment, the ceramic of step (a) has the formula Li 1+z Al z M 2-z (PO4)3, where M is Ti, Ge, or a combination thereof, and 0 < z < 1. In one embodiment, M is Ge. In another embodiment, M is Ti. In a further embodiment, step (a) further comprises pressing the mixture in the presence of oxygen (e.g., in air), for example, at a pressure of 100 kg / cm 2 to 5000 kg / cm 2 .

[0034] In a further embodiment, the method comprises step (c)(ii) and the method comprises removing the first and second carriers before bringing the electrode material layer into contact with the solid electrolyte layer. Alternatively, the method comprises step (c)(ii) and the method comprises removing the first and second carriers after bringing the electrode material layer into contact with the solid electrolyte layer.

[0035] In yet another embodiment, the method further comprises laminating the bilayer material between rollers before step (d).

[0036] According to other embodiments, step (b) further comprises a solvent and step (c) further comprises drying the applied electrode material. In another embodiment, step (b) comprises dry-mixing the electrochemically active material, ceramic particles, and electronically conductive material, suspending the resulting mixture and a polymer in a solvent, and step (c) further comprises drying the applied electrode material.

[0037] In another embodiment, step (d) is carried out in an inert atmosphere (e.g., in argon, nitrogen). In a further embodiment, step (d) is carried out at a pressure of 50 kg / cm 2 to 5000 kg / cm 2 , or 100 kg / cm 2 to 5000 kg / cm 2 , or 300 kg / cm 2 to 2000 kg / cm 2 . In yet another embodiment, step (d) is carried out at a temperature of about 450 °C to about 850 °C or about 600 °C to about 750 °C. In another embodiment, step (d) is carried out for a time greater than 0 hours and less than 10 hours, or 30 minutes to 5 hours, or 30 minutes to 2 hours.

[0038] In one embodiment, the electrode layer is a positive electrode layer. In one embodiment, the electrochemically active material in the electrode layer is selected from phosphates (e.g., LiM a PO4, where Ma is Fe, Ni, Mn, Co, or a combination thereof), oxides, and composite oxides, such as LiMn2O4, LiM b O2 (where M b is Mn, Co, Ni, or a combination thereof) and Li(NiM c )O2 (where M c is Mn, Co, Al, Fe, Cr, Ti, Zr, or a combination thereof), elemental sulfur, elemental selenium, iron(III) fluoride, copper(II) fluoride, lithium iodide, and iodine. For example, the electrochemically active material of the positive electrode can be phosphate LiM a PO4, where M a is Fe, Mn, Co, or a combination thereof (such as LiFePO4), and the electrochemically active material is made of particles optionally coated with carbon.

[0039] In a further embodiment, the electronically conductive material in the electrode layer is selected from carbon black, Ketjen TM black, acetylene black, graphite, graphene, carbon fiber, or nanofiber (such as VGCF), carbon nanotubes, and combinations thereof. In one example, the electronically conductive material comprises carbon fiber (such as VGCF). In another example, the electronically conductive material comprises graphite.

[0040] In yet another embodiment, the ceramic particles in step (b) comprise a ceramic of the formula Li 1+z Al z M 2-z (PO4)3, where M is Ti, Ge, or a combination thereof, and 0 < z < 1. In one example, M is Ge. In another example, M is Ti.

[0041] In a related aspect, the ceramic in step (a) is the same as the ceramic in step (b).

[0042] According to another aspect, the present invention relates to a multilayer assembly obtained by the method as defined herein.

[0043] According to yet another aspect, the present invention relates to a multilayer assembly comprising a solid electrode layer and a solid electrolyte layer, wherein:

[0044] the solid electrolyte layer comprises ceramic particles;

[0045] the solid electrode layer comprises an electrochemically active material, ceramic particles, and an electronically conductive material; and

[0046] the solid electrode layer and the solid electrolyte layer do not contain a polymer electrolyte and a polymer binder.

[0047] In one embodiment, the ceramic in the solid electrolyte layer has the formula Li 1+z Alz M 2-z (PO4)3, where M is Ti, Ge, or a combination thereof, and 0 < z < 1. In one instance, M is Ge. In another instance, M is Ti.

[0048] In one embodiment, the electrode is a positive electrode. In one embodiment, the electrochemically active material is selected from phosphates (such as LiM a PO4, where M a is Fe, Ni, Mn, Co, or a combination thereof), oxides, and composite oxides, such as LiMn2O4, LiM b O2 (M b is Mn, Co, Ni, or a combination thereof) and Li(NiM c )O2 (M c is Mn, Co, Al, Fe, Cr, Ti, Zr, or a combination thereof), elemental sulfur, elemental selenium, iron(III) fluoride, copper(II) fluoride, lithium iodide, and iodine. For example, the electrochemically active material of the positive electrode can be the phosphate LiM a PO4, where M a is Fe, Mn, Co, or a combination thereof (such as LiFePO4), where the electrochemically active material consists of particles optionally coated with carbon.

[0049] In a further embodiment, the electronically conductive material is selected from carbon black, Ketjen TM black, acetylene black, graphite, graphene, carbon fiber or nanofiber (such as VGCF), carbon nanotubes, and combinations thereof. In one instance, the electronically conductive material comprises carbon fiber (such as VGCF). In another instance, the electronically conductive material comprises graphite.

[0050] In yet another embodiment, the ceramic particles in the solid electrode layer comprise a ceramic of the formula Li 1+z Al z M 2-z (PO4)3, where M is Ti, Ge, or a combination thereof, and 0 < z < 1. In one instance, M is Ge. In another instance, M is Ti.

[0051] In a preferred embodiment, the ceramic particles in the solid electrolyte layer are the same as the ceramic particles in the solid electrode layer.

[0052] In a further embodiment, the multilayer assembly described herein or prepared by the methods described herein comprises a high contact portion, i.e., a tightly fused interface, at the interface between the solid electrolyte layer and the solid electrode layer.

[0053] In another embodiment, the multilayer assembly described herein or prepared by one of the present methods has a high density, for example, wherein at least one layer of the multilayer assembly has a density of at least 90% of the theoretical density, for example, the multilayer assembly has a density of at least 90% of the theoretical density.

[0054] In a further aspect, an electrochemical cell is described herein, comprising a negative electrode, a positive electrode and an electrolyte, wherein the electrolyte and the positive electrode together form a multilayer assembly as defined herein. In one embodiment, the negative electrode comprises a lithium or lithium alloy film and a polymer interlayer between the lithium or lithium alloy film and the solid electrolyte layer. For example, the polymer interlayer comprises a polyether polymer and a lithium salt, such as an optionally cross-linked PEO-based polymer and a lithium salt (e.g., LiTFSI).

[0055] According to another aspect, the present invention relates to a method for preparing an electrochemical cell, comprising the steps of:

[0056] (i) preparing a multilayer assembly according to a method as defined herein; and

[0057] (ii) Assembling the multilayer assembly of step (i) with the negative electrode layer.

[0058] In one embodiment, the negative electrode layer comprises a lithium or lithium alloy film and a polymer interlayer between the lithium or lithium alloy film and the solid electrolyte layer. For example, the polymer interlayer comprises a polyether polymer and a lithium salt, such as an optionally cross-linked PEO-based polymer and a lithium salt (such as LiTFSI).

[0059] A further aspect relates to a battery comprising at least one electrochemical cell as defined herein, such as a lithium battery or a lithium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] Figure 1 One embodiment of the method is schematically shown.

[0061] Figure 2 X-ray diffraction patterns of (a) LAGP before sintering and (b) LAGP after sintering at 1000°C are shown.

[0062] Figure 3 The first two charge / discharge curves of a battery prepared according to one embodiment of the present method when cycled at a current of 100 μA are shown.

[0063] Figure 4 The charge / discharge curves of a battery prepared according to the embodiment described in Example 2 are shown. DETAILED DESCRIPTION

[0064] The following detailed description and examples are exemplary and should not be construed to further limit the scope of the present invention.

[0065] All technical and scientific terms and words used herein have the same definitions as commonly understood by those skilled in the art to which this technology pertains. Nevertheless, for clarity, definitions of some terms and words used are provided below.

[0066] When the term "about" is used herein, it means approximately, around, and in the neighborhood of. When the term "about" is used with respect to a value, it modifies the value, for example, a 10% variation above and below its nominal value. This term may also take into account the probability of random error in experimental measurements or rounding of values.

[0067] The phrases "free of polymers," "free of polymer binders," "excluding polymers," or "excluding polymer binders" are equivalent and mean that the characterized material (electrolyte or electrode) does not contain polymers commonly used in electrolytes or as binders for electrode materials (e.g., PEO-based polymers, fluorinated polymers, poly(alkylene carbonates), polyvinyl butyral, polyvinyl alcohol, etc.). However, the phrase is not intended to exclude carbon-based macromolecules (such as graphene, carbon nanotubes, carbon fibers, etc.) that serve as electronically conductive materials in electrode materials.

[0068] The term "support" as used herein refers to a material to which a mixture, such as a slurry, is applied, typically in the form of a film or foil. The support material is non-reactive to the mixture applied thereto. Examples of materials used as supports include polymeric supports such as polypropylene, polyethylene, and other inert polymers.

[0069] The term "lithium salt" as used herein refers to any lithium salt that can be used in a solid electrolyte for an electrochemical cell. Non-limiting examples of lithium salts include lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), 2-trifluoromethyl-4,5-dicyanoimidazole lithium (LiTDI), 4,5-dicyano-1,2,3-triazole lithium (LiDCTA), lithium bis(pentafluoroethylsulfonyl)imide (LiBETI), lithium tetrafluoroborate (LiBF4), lithium bis(oxalate)borate (LiBOB), lithium nitrate (LiNO3), lithium chloride (LiCl), lithium bromide (LiBr), lithium fluoride (LiF), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium trifluoromethanesulfonate (LiSO3CF3) (LiTf), lithium fluoroalkyl phosphate Li[PF3(CF2CF3)3] (LiFAP), lithium tetrakis(trifluoroacetoxy)borate Li[B(OCOCF3)4] (LiTFAB), lithium bis(1,2-benzenediol(2-)-O,O')borate Li[B(C6O2)2] (LBBB).

[0070] This article relates to the preparation of solid multilayer electrode-electrolyte assemblies. This method avoids the use of polymers in the electrolyte or as binders in the electrodes of the final material. Two versions of this method are described. The first version does not include polymers during the preparation of the multilayer, while the second version omits the polymer used during the hot pressing step. The first version of the method generally does not require a solvent. Figure 1 One embodiment of the method is shown, which shows hot pressing the solid electrode and electrolyte layers together.

[0071] Although high temperature sintering of cathode materials under oxygen may lead to combustion of a portion of the cathode material, LAGP and LATP were found to be greatly affected when sintered under an inert atmosphere. For these ceramics, gaseous oxygen is subsequently lost, thereby forming germanium (II) or titanium (II) oxides and lithium phosphate impurities (see Figure 2 ).

[0072] Therefore, a novel method for preparing an assembly comprising at least two layers (including a ceramic-based electrolyte layer and an electrode layer) for electrochemical applications is proposed herein. The method is simple and quite short. One of the schemes also avoids the use of toxic and / or flammable solvents. It also ensures good contact at the interface between the electrolyte and the electrode solid layer, where the two layers are tightly bonded (fused) to each other. The electrode-electrolyte solid assembly also has a density suitable for its use in an electrochemical cell.

[0073] One example of such a method for preparing a multilayer assembly comprises at least the steps of:

[0074] a) preparing a solid electrolyte layer by compressing particles comprising a ceramic;

[0075] b) preparing a mixture comprising at least an electrochemically active material, ceramic particles and an electronically conductive material, said mixture being free of solvent;

[0076] c) applying the mixture prepared in (b) onto the solid electrolyte layer prepared in (a) to obtain a double-layer material;

[0077] d) at least 50 kg / cm 2 , or 50kg / cm 2 Up to 5000kg / cm 2 and pressing the double-layer material obtained in (c) at a temperature of about 400° C. to about 900° C., or about 450° C. to about 850° C., or about 600° C. to about 700° C. under a pressure of 100° C.

[0078] For example, step (a) of the present method avoids the use of solvents and / or lithium salts. The solid electrolyte layer and the solid electrode layer of the assembly are free of polymers (ie, polymers of the solid polymer electrolyte or polymer binder).

[0079] Any ceramic known to those skilled in the art can be used in this method. The selected ceramic is suitable as an electrolyte ceramic and is stable under the process conditions. For example, the ceramic in the solid electrolyte layer can be of the formula Li 1+z Al z M 2-z (PO4)3, where M is Ti, Ge, or a combination thereof, and 0 < z < 1. According to one example, M is Ge. According to another example, M is Ti. For example, z is in the range of 0.25 to 0.75, or 0.1 to 0.9, or 0.3 to 0.7, or 0.4 to 0.6, or approximately 0.5. The ceramic can have a structure similar to NASICON.

[0080] The solid electrolyte layer can have a final thickness (after step (d)) of less than 1 mm, or in the range of 50 μm to 1 mm, or 50 μm to 500 μm, or 50 μm to 200 μm.

[0081] The solid electrolyte layer is preferably compressed in step (a) without external heating and in the presence of oxygen (e.g., in air). The bilayer material after adding the electrode layer mixture is preferably hot-pressed in step (d) in an inert atmosphere (e.g., under argon, nitrogen).

[0082] For example, step (a) can be carried out at a pressure of 100 kg / cm 2 to 5000 kg / cm 2 .

[0083] The hot-pressing step (d) can be carried out for a time greater than 0 hours and less than 10 hours, or 30 minutes to 5 hours, or 30 minutes to 2 hours. The hot-pressing step can be carried out in a heating chamber, such as an oven, furnace, etc., while applying pressure to at least one side of the bilayer material. Preferably, the hot-pressing step is carried out using a hot-pressing furnace, hot-pressing die head, etc. The bilayer material is usually contained in a mold and pressure is applied unidirectionally.

[0084] The mixing step (b) in this method can be carried out by any method known in the art, such as ball milling, planetary mixer, etc. For example, the mixing step can be carried out by ball milling using zirconia (zirconium dioxide) balls.

[0085] Alternatively, a method for preparing a multilayer assembly comprising a solid electrode layer and a solid electrolyte layer at least includes the steps of:

[0086] a) preparing a solid electrolyte layer by applying a mixture of ceramic particles and a polymer on a first carrier;

[0087] b) preparing a mixture comprising at least an electrochemically active material, ceramic particles, an electronically conductive material, and optionally a polymer;

[0088] c) Apply the electrode material mixture prepared in step (b):

[0089] i. Onto the solid electrolyte layer prepared in step (a); or

[0090] ii. Onto a second carrier and then bring the surface of the applied electrode material mixture into contact with the surface of the solid electrolyte layer;

[0091] To provide a bilayer material;

[0092] d) Press the bilayer material obtained in (c) at a pressure of at least 50 kg / cm 2 and a temperature of about 400 °C to about 900 °C.

[0093] Step (a) of the method may not include adding a solvent. Alternatively, step (a) of the method further includes a solvent and a step of drying the mixture after application. In one example, step (a) further includes removing the first carrier. Preferably, step (a) does not include adding a lithium salt.

[0094] Non-limiting examples of polymers that can be used in step (a) and optional step (b) (if present) include, independently at each occurrence, fluorinated polymers (such as polyvinylidene fluoride (PVDF), or poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP)), poly(alkylene carbonate) (such as poly(ethylene carbonate) or poly(propylene carbonate)), polyvinyl butyral (PVB) or polyvinyl alcohol (PVA). For example, the polymer is poly(alkylene carbonate) (such as poly(ethylene carbonate) or poly(propylene carbonate)). The solid electrolyte layer and the electrode layer do not contain polymers after step (d).

[0095] The ceramic in step (a) is, for example, of the formula Li 1+z Al z M 2-z (PO4)3, where M is Ti, Ge, or a combination thereof, and z is such that 0 < z < 1. Step (a) may further include pressing the mixture in the presence of oxygen (such as oxygen from air), for example, at a pressure of 100 kg / cm 2 to 5000 kg / cm 2 .

[0096] In one example, the method includes step (c)(ii) and the method includes removing the first carrier and the second carrier before bringing the electrode material layer into contact with the solid electrolyte layer. Alternatively, the method includes step (c)(ii) and the method includes removing the first carrier and the second carrier after bringing the electrode material layer into contact with the solid electrolyte layer.

[0097] The method preferably further comprises laminating the two-layer material between rollers prior to step (d).

[0098] In other examples, step (b) further includes a solvent and step (c) further includes drying the applied electrode material. For example, step (b) may include dry mixing the electrochemically active material, the ceramic particles, and the electronically conductive material, suspending the resulting mixture with the polymer in a solvent, and then drying the applied electrode material.

[0099] Step (d) can be carried out under an inert atmosphere (e.g., argon or nitrogen). This step can also be carried out under 50 kg / cm 2 Up to 5000kg / cm 2 , or 100kg / cm 2 Up to 5000kg / cm 2 , or 300kg / cm 2 Up to 2000kg / cm 2 The temperature applied in step (d) may be in the range of about 450°C to about 850°C or about 600°C to about 750°C. This step is preferably carried out for a time greater than 0 hours and less than 10 hours, or 30 minutes to 5 hours, or 30 minutes to 2 hours.

[0100] The solid electrolyte layer may have a final thickness of less than 1 mm, or in the range of 50 μm to 1 mm, or 50 μm to 500 μm, or 50 μm to 200 μm. The total thickness of the double layer material comprising the electrode layer and the electrolyte is preferably less than 1 mm, or in the range of 50 μm to 1 mm, or 50 μm to 600 μm, or 100 μm to 400 μm.

[0101] In any of the methods of the present invention, the electrode layer of the multilayer assembly is preferably a positive electrode. For example, the electrode layer contains about 25% to about 60% by weight of electrochemically active material, about 25% to about 60% by weight of ceramic particles, and about 5% to about 15% by weight of electronically conductive material, the total amount being 100%.

[0102] Non-limiting examples of electrochemically active materials include phosphates (e.g., LiM a PO4, of which M a Fe, Ni, Mn, Co or a combination thereof), oxides and composite oxides, such as LiMn2O4, LiM b O2(M b is Mn, Co, Ni or a combination thereof) and Li (NiM c )O2(M cis Mn, Co, Al, Fe, Cr, Ti, Zr, or a combination thereof), elemental sulfur, elemental selenium, iron(III) fluoride, copper(II) fluoride, lithium iodide, and iodine. In some instances, the electrochemically active material of the positive electrode is phosphate LiM a PO4, where M a is Fe, Mn, Co, or a combination thereof (such as LiFePO4), where the electrochemically active material is made of particles optionally further coated with carbon.

[0103] The electronically conductive material contained in the electrode layer can be selected from carbon black, Ketjen TM black, acetylene black, graphite, graphene, carbon fiber, or nanofiber (such as VGCF), carbon nanotubes, and combinations thereof. For example, the electronically conductive material contains carbon fiber (such as VGCF) or graphite.

[0104] For example, the ceramic particles in the electrode layer contain a compound of the formula Li 1+z Al z M 2-z (PO4)3, where M is Ti, Ge, or a combination thereof, and 0 < z < 1. In one instance, M is Ge. In another instance, M is Ti. For example, z is between 0.25 and 0.75, or z is about 0.5.

[0105] In some instances, the ceramics in the solid electrolyte layer and the ceramic particles in the solid electrode layer contain the same compound.

[0106] Also designed herein are multilayer assemblies obtainable or obtained by this method. For example, the multilayer assembly includes a tightly fused interface between the solid electrolyte layer and the solid electrode layer. The solid electrolyte layer and the solid electrode layer each have a high density. For example, the density of at least one of the two layers is at least 90% of the theoretical density.

[0107] Also provided herein is an electrochemical cell comprising a negative electrode, a positive electrode, and an electrolyte, where the electrolyte and the positive electrode form a multilayer assembly as defined herein or obtained by this method. For example, the negative electrode includes a lithium or lithium alloy film and a polymer interlayer between the lithium or lithium alloy film and the solid electrolyte layer. The polymer interlayer can include, for example, a polyether polymer and a lithium salt, such as an optionally crosslinked PEO-based polymer and a lithium salt (such as LiTFSI).

[0108] Also designed is a method for preparing an electrochemical cell as defined herein. Such a method includes:

[0109] (i) preparing a multilayer assembly according to the method as defined herein; and

[0110] (ii) assembling the multilayer assembly of step (i) with a negative electrode layer.

[0111] For example, the negative electrode layer comprises a lithium or lithium alloy film and a polymer intermediate layer as described above between the lithium or lithium alloy film and the solid electrolyte layer.

[0112] The present specification also describes a battery comprising at least one electrochemical cell as defined herein. For example, the battery is a lithium battery or a lithium ion battery.

[0113] The present technology further relates to the use of the present electrochemical cells and batteries, for example in mobile devices, such as mobile phones, cameras, tablets or laptops, in electric vehicles or hybrid vehicles or in renewable energy storage.

[0114] Example

[0115] The following non-limiting examples are exemplary embodiments and should not be construed as further limiting the scope of the present invention.These examples are better understood with reference to the accompanying drawings.

[0116] Embodiment 1:

[0117] (a) Solid electrolyte-cathode assembly

[0118] Li 1.5 Al 0.5 Ge 1.5 (PO4)3 (0.75 g, LAGP) powder was cold pressed in a 16 mm titanium-zirconium-molybdenum (TZM) mold under air with a 5 ton (5000 kg) weight to form LAGP electrolyte pellets. 0.75 grams of a mixture containing carbon-coated LiFePO4 (45 wt%), LAGP (45 wt%) and vapor-grown carbon fiber (VGCF, 10 wt%) was added to the LAGP electrolyte pellets to form a double-layer material. This double-layer material was then pressed in a hot press at 650°C under an inert atmosphere with a 2 ton (2000 kg) pressure for 1 hour to produce a solid electrolyte-cathode assembly.

[0119] (b) All-solid-state electrochemical battery

[0120] The solid electrolyte-cathode assembly obtained in (a) was assembled with a metallic lithium film and a protective layer comprising PEO and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) (O / Li molar ratio of 20:1) between the metallic lithium anode and the ceramic electrolyte.

[0121] The cell was cycled at 100 μA and the charge / discharge results showed 100% efficiency after 50 hours of cycling. Figure 3 Potential vs. capacity for the first two cycles are shown.

[0122] Embodiment 2:

[0123] LAGP (85 wt%) and 25 (poly(ethylene carbonate), 15 wt%) was dispersed in N,N-dimethylformamide or N,N-dimethylformamide:tetrahydrofuran (1:1) mixture. The resulting mixture was applied to a polypropylene film with a doctor blade. The film was then dried at 50°C for 2 hours.

[0124] By using The cathode was prepared by mixing LAGP (45%), LiFePO4 (45%) and graphite (10%) in a mixer to obtain a mixed positive electrode material. 25 (15%) was dispersed in N,N-dimethylformamide or N,N-dimethylformamide:tetrahydrofuran (1:1) mixture. The resulting mixture was applied as a film on a polypropylene film using a doctor blade. The cathode thus formed was dried at 50°C for 2 hours.

[0125] The self-supporting LAGP electrolyte membrane and cathode membrane were then separated from the polypropylene membrane and laminated together at 80°C to reduce the porosity and obtain a ceramic-cathode membrane with a thickness of 100 to 400 μm. The membrane was then polished and hot-pressed at 700°C for 1 hour with a pressure of 112 MPa. The hot-pressed solid ceramic electrolyte-cathode assembly was cycled with lithium metal, and the results showed that Figure 4 middle.

[0126] Many modifications may be made to any of the above-described embodiments without departing from the scope of the invention.All references, patents or scientific literature materials mentioned in this application are hereby incorporated by reference in their entirety for all purposes.

Claims

1. A method for preparing a multilayer assembly comprising a solid electrode layer and a solid electrolyte layer, the method comprising at least the steps of: a) preparing a solid electrolyte layer by compressing ceramic particles; b) preparing a mixture comprising at least an electrochemically active material, ceramic particles and an electronically conductive material, said mixture being free of solvent; c) applying the mixture prepared in (b) onto the solid electrolyte layer prepared in (a) to obtain a double-layer material; and d) at least 50 kg / cm 2 and pressing the double-layer material obtained in (c) at a temperature in the range of 400° C. to 900° C., wherein step (b) does not include the addition of a solvent, and Therein, no polymer is included in the production process of the multilayer assembly.

2. The method of claim 1, wherein step (a) does not comprise the addition of a solvent.

3. The method of claim 1, wherein step (a) does not include adding a lithium salt.

4. The method of any one of claims 1 to 3, wherein the ceramic of step (a) has the formula Li 1+z Al z M 2-z (PO4)3, wherein M is Ti, Ge or a combination thereof, and z is such that 0 <z<1。 5. The method of claim 4, wherein M is Ge.

6. The method of claim 4, wherein M is Ti.

7. The process of any one of claims 1 to 3, wherein step (a) is carried out in the presence of oxygen.

8. The method of any one of claims 1 to 3, wherein the compression of the particles in step (a) is 100 kg / cm 2 Up to 5000kg / cm 2 The pressure is within the range of .

9. The process of any one of claims 1 to 3, wherein step (d) is performed in an inert atmosphere.

10. The method of any one of claims 1 to 3, wherein step (d) is carried out at 50 kg / cm 2 Up to 5000kg / cm 2 The pressure is within the range of .

11. The method of claim 10, wherein step (d) is carried out at 100 kg / cm 2 Up to 5000kg / cm 2 The pressure is within the range of .

12. The method of claim 10, wherein step (d) is carried out at 300 kg / cm 2 Up to 2000kg / cm 2 The pressure is within the range of .

13. The process of any one of claims 1 to 3, wherein step (d) is performed at a temperature in the range of 450°C to 850°C.

14. The method of claim 13, wherein step (d) is performed at a temperature in the range of 600°C to 700°C.

15. The method of any one of claims 1 to 3, wherein step (d) is performed for a time greater than 0 hours and less than 10 hours.

16. The method of claim 15, wherein step (d) is performed for 30 minutes to 5 hours.

17. The method of claim 15, wherein step (d) is performed for 30 minutes to 2 hours.

18. The method of any one of claims 1 to 3, wherein the preparation of the mixture in step (b) is carried out by ball milling.

19. The method of any one of claims 1 to 3, wherein the electrode is a cathode.

20. The method of any one of claims 1 to 3, wherein the electrochemically active material is selected from phosphates, oxides and composite oxides, elemental sulfur, elemental selenium, iron (III) fluoride, copper (II) fluoride, lithium iodide and iodine.

21. The method of claim 20, wherein the electrochemically active material is of the formula LiM a PO4 phosphate, where M a It is Fe, Ni, Mn, Co or a combination thereof.

22. The method of claim 21, wherein M a is Fe, Mn, Co or a combination thereof, wherein the electrochemically active material is made of particles that are optionally further coated with carbon.

23. The method of claim 22, wherein the formula LiM a The phosphate of PO4 is LiFePO4.

24. The method of claim 20, wherein the electrochemically active material is selected from the group consisting of LiMn2O4, LiM b O2 and Li(NiM c )O2 oxide, where M b is Mn, Co, Ni or a combination thereof, M c It is Mn, Co, Al, Fe, Cr, Ti, Zr or a combination thereof.

25. The method of any one of claims 1 to 3, wherein the electronically conductive material is selected from carbon black, Ketjen TM Black, acetylene black, graphite, graphene, carbon fibers or nanofibers, carbon nanotubes, and combinations thereof.

26. The method of claim 25, wherein the electronically conductive material comprises carbon fibers.

27. The method of any one of claims 1 to 3, wherein the ceramic particles of step (b) comprise the formula Li 1+z Al z M 2-z (PO4)3 ceramics, wherein M is Ti, Ge or a combination thereof, and 0 <z<1。 28. The method of claim 27, wherein M is Ge.

29. The method of claim 27, wherein M is Ti.

30. The method of any one of claims 1 to 3, wherein the ceramic of step (a) and the ceramic particles of step (b) are the same.

31. A method for preparing a multilayer assembly comprising a solid electrode layer and a solid electrolyte layer, the method comprising at least the steps of: a) preparing an electrolyte composition layer by applying a mixture of ceramic particles and a polymer on a first support; b) preparing a mixture comprising at least an electrochemically active material, ceramic particles, an electronically conductive material and optionally a polymer; c) mixing the electrode material mixture prepared in step (b) i. applied to the electrolyte composition layer prepared in step (a); or ii. applied to a second support, and then contacting the surface of the applied electrode material mixture with the surface of the electrolyte composition layer; Provide double layer material; d) at least 50 kg / cm 2 pressing the double-layer material obtained in step c) at a pressure of 100° C. and at a temperature in the range of 400° C. to 900° C., wherein the solid electrolyte layer and the electrode layer are free of polymer after step (d).

32. The method of claim 31, wherein step (a) does not comprise adding a solvent.

33. The method of claim 31, wherein step (a) further comprises a solvent and comprises drying the mixture after applying.

34. The method of claim 31, wherein step (a) further comprises removing the first support.

35. The method of claim 31, wherein step (a) does not comprise adding a lithium salt.

36. The method of claim 31, wherein the polymer of step (a) and step (b), if present, is independently selected at each occurrence from a fluorinated polymer, a poly(alkylene carbonate), polyvinyl butyral (PVB), or polyvinyl alcohol (PVA).

37. The method of claim 36, wherein the polymer is a poly(alkylene carbonate).

38. The method of claim 37, wherein the poly(alkylene carbonate) is poly(ethylene carbonate) or poly(propylene carbonate).

39. The method of any one of claims 31 to 38, wherein the ceramic of step (a) has the formula Li 1+z Al z M 2-z (PO4)3, wherein M is Ti, Ge or a combination thereof, and 0 <z<1。 40. The method of claim 39, wherein M is Ge.

41. The method of claim 39, wherein M is Ti.

42. The method of any one of claims 31 to 38, wherein step (a) further comprises pressing the mixture in the presence of oxygen.

43. The method of claim 42, wherein the pressing is performed at 100 kg / cm 2 Up to 5000kg / cm 2 The pressure is within the range of .

44. The method of any one of claims 31 to 38, wherein the method comprises step (c)(ii) and the method comprises removing the first support and the second support prior to contacting.

45. The method of any one of claims 31 to 38, wherein the method comprises step (c)(ii) and the method comprises removing the first support and the second support after contacting and before step (d).

46. ​​The method of any one of claims 31 to 38, wherein the method further comprises the step of laminating the bi-layer material between rollers prior to step (d).

47. The method of any one of claims 31 to 38, wherein step (b) further comprises a solvent and step (c) further comprises drying the applied electrode material.

48. The method of any one of claims 31 to 38, wherein step (b) comprises dry mixing the electrochemically active material, the ceramic particles and the electronically conductive material, suspending the resulting mixture with a polymer in a solvent, and step (c) further comprises drying the applied electrode material.

49. The process of any one of claims 31 to 38, wherein step (d) is performed in an inert atmosphere.

50. The method of any one of claims 31 to 38, wherein step (d) is carried out at 50 kg / cm 2 Up to 5000kg / cm 2 The pressure is within the range of .

51. The method of claim 50, wherein step (d) is carried out at 100 kg / cm 2 Up to 5000kg / cm 2 The pressure is within the range of .

52. The method of claim 50, wherein step (d) is carried out at 300 kg / cm 2 Up to 2000kg / cm 2 The pressure is within the range of .

53. The process of any one of claims 31 to 38, wherein step (d) is carried out at a temperature of 450°C to 850°C.

54. The process of claim 53, wherein step (d) is performed at a temperature of 600°C to 750°C.

55. The method of any one of claims 31 to 38, wherein step (d) is performed for a time greater than 0 hours and less than 10 hours.

56. The method of claim 55, wherein step (d) is performed for 30 minutes to 5 hours.

57. The method of claim 55, wherein step (d) is performed for 30 minutes to 2 hours.

58. The method of any one of claims 31 to 38, wherein the preparation of the mixture in step (b) is carried out by ball milling.

59. The method of any one of claims 31 to 38, wherein the electrode layer is a positive electrode layer.

60. The method of any one of claims 31 to 38, wherein the electrochemically active material is selected from phosphates, oxides and composite oxides, elemental sulfur, elemental selenium, iron (III) fluoride, copper (II) fluoride, lithium iodide and iodine.

61. The method of claim 60, wherein the electrochemically active material is of the formula LiM a PO4 phosphate, where M a It is Fe, Ni, Mn, Co or a combination thereof.

62. The method of claim 61, wherein M a is Fe, Mn, Co or a combination thereof, wherein the electrochemically active material is made of particles that are optionally further coated with carbon.

63. The method of claim 62, wherein the formula LiM a The phosphate of PO4 is LiFePO4.

64. The method of claim 60, wherein the electrochemically active material is selected from the group consisting of LiMn2O4, LiM b O2 and Li(NiM c )O2 oxide, where M b is Mn, Co, Ni or a combination thereof, M c It is Mn, Co, Al, Fe, Cr, Ti, Zr or a combination thereof.

65. The method of any one of claims 31 to 38, wherein the electronically conductive material is selected from carbon black, Ketjen TM Black, acetylene black, graphite, graphene, carbon fibers or nanofibers, carbon nanotubes, and combinations thereof.

66. The method of claim 65, wherein the electronically conductive material comprises carbon fiber (such as VGCF).

67. The method of claim 65, wherein the electronically conductive material comprises graphite.

68. The method of any one of claims 31 to 38, wherein the ceramic particles of step (b) comprise the formula Li 1+z Al z M 2-z (PO4)3 ceramics, wherein M is Ti, Ge or a combination thereof, and 0 <z<1。 69. The method of claim 68, wherein M is Ge.

70. The method of claim 68, wherein M is Ti.

71. The method of any one of claims 31 to 38, wherein the ceramic in step (a) and the ceramic particles in step (b) are the same.

72. A multilayer assembly obtainable by a method as claimed in any one of claims 1 to 71.

73. A multilayer assembly comprising a solid electrode layer and a solid electrolyte layer, wherein: The solid electrolyte layer comprises ceramic particles; The solid electrode layer comprises an electrochemically active material, ceramic particles and an electronically conductive material; and The solid electrode layer and the solid electrolyte layer do not contain electrolyte polymers and polymer binders, Wherein the multilayer assembly comprises a high contact at the interface between the solid electrolyte layer and the solid electrode layer.

74. The multilayer assembly of claim 73, wherein the ceramic in the solid electrolyte layer has the formula Li 1+z Al z M 2-z (PO4)3, wherein M is Ti, Ge or a combination thereof, and 0 <z<1。 75. The multi-layer assembly of claim 74, wherein M is Ge.

76. The multi-layer assembly of claim 74, wherein M is Ti.

77. The multi-layer assembly of any one of claims 73 to 76, wherein the electrode layer is a positive electrode layer.

78. The multilayer assembly of any one of claims 73 to 76, wherein the electrochemically active material is selected from phosphates, oxides and complex oxides, elemental sulfur, elemental selenium, iron (III) fluoride, copper (II) fluoride, lithium iodide and iodine.

79. The multilayer assembly of claim 78, wherein the electrochemically active material is of the formula LiM a PO4 phosphate, where M a It is Fe, Ni, Mn, Co or a combination thereof.

80. The multilayer assembly of claim 79, wherein M a is Fe, Mn, Co or a combination thereof, wherein the electrochemically active material is made of particles that are optionally coated with carbon.

81. The multilayer assembly of claim 80, wherein the formula LiM a The phosphate of PO4 is LiFePO4.

82. The multilayer assembly of claim 78, wherein the electrochemically active material is selected from the group consisting of LiMn2O4, LiM b O2 and Li(NiM c )O2 oxide, where M b is Mn, Co, Ni or a combination thereof, M c It is Mn, Co, Al, Fe, Cr, Ti, Zr or a combination thereof.

83. The multilayer assembly of any one of claims 73 to 76, wherein the conductive material is selected from carbon black, Ketjen TM Black, acetylene black, graphite, graphene, carbon fibers or nanofibers, carbon nanotubes, and combinations thereof.

84. The multi-layer assembly of claim 83, wherein the electronically conductive material comprises carbon fibers.

85. The multi-layer assembly of claim 83, wherein the electronically conductive material comprises graphite.

86. The multilayer assembly of any one of claims 73 to 76, wherein the ceramic particles in the solid electrode layer comprise the formula Li 1+z Al z M 2-z (PO4)3 ceramics, wherein M is Ti, Ge or a combination thereof, and 0 <z<1。 87. The multi-layer assembly of claim 86, wherein M is Ge.

88. The multi-layer assembly of claim 86, wherein M is Ti.

89. The multi-layer assembly of any one of claims 73 to 76, wherein the ceramic particles in the solid electrolyte layer and the ceramic particles in the solid electrode layer are the same.

90. The multi-layer assembly of any one of claims 73 to 76, wherein at least one layer of the multi-layer assembly has a density of at least 90% of the theoretical density.

91. An electrochemical cell comprising a negative electrode, a positive electrode and an electrolyte, wherein the electrolyte and the positive electrode together form a multilayer assembly as claimed in any one of claims 72 to 90.

92. The electrochemical cell of claim 91, wherein the negative electrode comprises a lithium or lithium alloy film and a polymer interlayer between the lithium or lithium alloy film and the solid electrolyte layer.

93. The electrochemical cell of claim 92, wherein the polymer interlayer comprises a polyether polymer and a lithium salt.

94. The electrochemical cell of claim 93, wherein the polyether polymer is an optionally cross-linked PEO-based polymer.

95. A method for preparing an electrochemical cell comprising the steps of: (i) preparing a multilayer assembly according to a method as claimed in any one of claims 1 to 71; and (ii) Assembling the multilayer assembly of step (i) with the negative electrode layer.

96. The method of claim 95, wherein the negative electrode layer comprises a lithium or lithium alloy film and a polymer interlayer between the lithium or lithium alloy film and the solid electrolyte layer.

97. The method of claim 96, wherein the polymer interlayer comprises a polyether polymer and a lithium salt.

98. The method of claim 97, wherein the polyether polymer is an optionally cross-linked PEO-based polymer.

99. A battery comprising at least one electrochemical cell as claimed in any one of claims 91 to 94.

100. The battery of claim 99, wherein the battery is a lithium battery or a lithium ion battery.

Citation Information

Patent Citations

  • Method for producing ceramic laminate, and ceramic laminate produced by the production method

    CN102959788A